PENERAPAN MOTIF CAKRA PALAH PADA KAIN BATIK PRODUK UMKM BATIK LWO LWANG WENTAR KABUPATEN BLITAR - Laela Farndatul Alifah; Luh Suartini; Langen Bronto Sutrisno (Jurnal Pendidikan Seni Rupa Undiksha, 2026)
This study examined the application of the Cakra Palah motif on batik fabrics produced by UMKM Batik Lwang Wentar in Blitar Regency as a form of cultural transformation based on local wisdom. The main focus of the research included the process of motif implementation, visual form, and the symbolic meaning embedded within it. The method used was a descriptive-analytical qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The results showed that the implementation process involved several systematic stages, including conceptualization, pattern design, motif transfer, waxing, coloring, and finishing. Visually, the Cakra Palah motif displayed a complex geometric structure combined with supporting ornaments, resulting in a harmonious aesthetic composition. In terms of meaning, the motif represented life philosophy, self-awareness, and the relationship between humans, nature, and God. The transformation from the relief of Penataran Temple into batik media indicated a creative reinterpretation that was adaptive to techniques and contemporary needs. The role of UMKM was crucial in maintaining the sustainability of the motif through innovation, education, and marketing strategies. Thus, batik functioned not only as an economic product but also as a dynamic and sustainable medium of cultural preservation. Keywords: Cakra Palah, batik, symbolism, cultural transformation, UMKM